Androgen-Influenced Polarization of Activin A-Producing Macrophages Accompanies Post-pyelonephritic Renal Scarring - Hreha, Teri N.; Collins, Christina A.; Daugherty, Allyssa L.; Griffith, Jessie M.; Hruska, Keith A.; Hunstad, David A. (Frontiers in Immunology, 2020)
Ascending bacterial pyelonephritis, a form of urinary tract infection (UTI) that can result in hospitalization, sepsis, and other complications, occurs in ~250,000 US patients annually; uropathogenic Escherichia coli (UPEC) cause a large majority of these infections. Although UTIs are primarily a disease of women, acute pyelonephritis in males is associated with increased mortality and morbidity, including renal scarring and end-stage renal disease. Preclinical models of UTI have only recently allowed investigation of sex and sex-hormone effects on pathogenesis. We previously demonstrated that renal scarring after experimental UPEC pyelonephritis is augmented by androgen exposure; testosterone exposure increases both the severity of pyelonephritis and the degree of renal scarring in both male and female mice. Activin A is an important driver of scarring in noninfectious renal injury, as well as a mediator of macrophage polarization. In this work, we investigated how androgen exposure influences immune cell recruitment to the UPEC-infected kidney and how cell-specific activin A production affects post-pyelonephritic scar formation. Compared with vehicle-treated females, androgenized mice exhibited reduced bacterial clearance from the kidney, despite robust myeloid cell recruitment that continued to increase as infection progressed. Infected kidneys from androgenized mice harbored more alternatively activated (M2) macrophages than vehicle-treated mice, reflecting an earlier shift from a pro-inflammatory (M1) phenotype. Androgen exposure also led to a sharp increase in activin A-producing myeloid cells in the infected kidney, as well as decreased levels of follistatin (which normally antagonizes activin action). As a result, infection in androgenized mice featured prolonged polarization of macrophages toward a pro-fibrotic M2a phenotype, accompanied by an increase in M2a-associated cytokines. These data indicate that androgen enhancement of UTI severity and resulting scar formation is related to augmented local activin A production and corresponding promotion of M2a macrophage polarization.